Minimally invasive (mini-thoracotomy) versus median sternotomy in redo mitral valve surgery: A meta-analysis of observational studies. (November 2021) - Hussain, Azhar; Chacko, Jacob; Uzzaman, Mohsin; Hamid, Osama; Butt, Salman; Zakai, Saad Badar; Khan, Habib
Objective: Redo mitral valve surgery has traditionally been performed via a median sternotomy. It is often challenging and is associated with increased perioperative mortality. Advances in cardiac surgical techniques over the last two decades have led to an increase in the use of a minimally invasive approach via a right anterolateral mini-thoracotomy as opposed to a repeat median sternotomy. However, despite these advances, there is no general consensus on the best form of entry, and as of yet, there are no randomized controlled trials. We performed a meta-analysis of observational studies to aid in determining the best approach for redo mitral valve surgery. Method: The MEDLINE and EMBASE databases were conducted up until 1 June 2020. Data regarding mortality, stroke, reoperation for bleeding and length of hospital stay, wound infection and cardiopulmonary bypass time were extracted and submitted to a meta-analysis using random effects modelling and the I 2 -test for heterogeneity. Seven retrospective observational studies were included, enrolling a total of 1070 patients. Results: There were a total of 1070 patients. Of these 364 had non-sternotomy approach compared with 707 patients who had median sternotomy. Further subgroup analysis revealed that 327 of the 364 patients had a mini-thoracotomy approach while the remaining 37 patients had a full thoracotomy approach. In-hospital mortality and length of stay were less in non-sternotomy group compared to median sternotomy group. There were no differences in stroke, CPB time and wound infections between the two groups. Conclusion: Redo mitral valve surgery can be performed safely with satisfactory outcomes via a mini-thoracotomy approach. This meta-analysis shows comparable results with reduced in-hospital mortality and hospital length of stay with a mini-thoracotomy approach.